2016
DOI: 10.1515/biol-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from protoplasts of Gentiana straminea Maxim

Abstract: A protocol is described for plant regeneration from protoplasts of Gentiana straminea Maxim. via somatic embryogenesis. Protoplasts were isolated from embryogenic calli in an enzyme solution composed of 2% Cellulase Onozuka R-10, 0.5% Macerozyme R-10, 0.5% Hemicellulase, and 0.5 M sorbitol with a yield of 3.0 × 106 protoplasts per gram of fresh weight. Liquid, solid-liquid double layer (sLD) and agar-pool (aPL) culture systems were used for protoplast culture. The aPL culture was the only method that produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Thus, within the framework of our researches we observed a different ratio of cell population being developed by cytodifferentiation. The morphology of the microcolonies obtained in the result of our study was common with the early stages of development of protoplasts of both Gentiana kurroo (Niedziela & Rybczyński, 2007) and G. straminea (Shi et al, 2016), which developed through direct somatic embryogenesis in specially selected plant lines in the deficiency of exogenous gibberellin. Related morphology has been observed, also in the initial division of the zygote in planta (Zhao & Sun, 2015) as well as polarization (formation by root-like projection) in the brown algae (Bogaert et al, 2013).…”
Section: Discussionsupporting
confidence: 63%
“…Thus, within the framework of our researches we observed a different ratio of cell population being developed by cytodifferentiation. The morphology of the microcolonies obtained in the result of our study was common with the early stages of development of protoplasts of both Gentiana kurroo (Niedziela & Rybczyński, 2007) and G. straminea (Shi et al, 2016), which developed through direct somatic embryogenesis in specially selected plant lines in the deficiency of exogenous gibberellin. Related morphology has been observed, also in the initial division of the zygote in planta (Zhao & Sun, 2015) as well as polarization (formation by root-like projection) in the brown algae (Bogaert et al, 2013).…”
Section: Discussionsupporting
confidence: 63%
“…In our work, the highest callus induction rate was obtained by using a combination of BAP and 2,4D. It has been demonstrated that the auxin 2,4-D is essential for the formation of the cell wall and the initial protoplast growth as previously observed in other species ( Shi et al., 2016 ; Tu et al., 2023 ). Although we failed in somatic embryo formation and plantlet regeneration under the procedure defined by us microcolonies and embryogenic callus formation were achieved and it provides a base for further optimization.…”
Section: Discussionsupporting
confidence: 82%
“…Another protocol for plant regeneration via SE from callus-derived protoplasts was developed for G. straminea (Shi et al, 2016). The agar-pool culture system was the only method that allows the production of embryogenic microcallus.…”
Section: Embryogenesis In Protoplast Culturesmentioning
confidence: 99%
“…A very high yield of regenerants via SE in protoplast bead culture confirmed the usefulness of this method for gentian cell manipulation. An efficient protocol for plant regeneration through SE was also developed for embryogenic cell suspension-derived protoplasts of G. macrophylla with the use of very similar culture conditions to those applied for protoplasts of G. straminea (Hu et al, 2015; Shi et al, 2016).…”
Section: Embryogenesis In Protoplast Culturesmentioning
confidence: 99%